CISA Certified Information Systems Auditor Practice Exams - Gregory, Peter (McGraw-Hill, 2020)
Publisher's Note: Products purchased from Third Party sellers are not guaranteed by the publisher for quality, authenticity, or access to any online entitlements included with the product. Hundreds of accurate practice questions that cover every topic on the latest version of the CISA exam Written by an IT security and audit expert, this highly effective self-study guide covers all five domains included on the 2019 release of the Certified Information Systems Auditor exam. To reinforce important skills and facilitate retention, every question is accompanied by explanations for both correct and incorrect answers. Designed to help you pass the test with greater confidence, this book is also an ideal companion to the bestselling CISA Certified Information Systems Auditor All-in-One Exam Guide, Fourth Edition. Covers all five exam domains: " Information Systems Auditing Process " Governance and Management of IT " Information Systems Acquisition, Development, and Implementation " Information Systems Operations and Business Resilience " Protection of Information Assets Online content includes: " 150 practice questions " Test engine that provides full-length practice exams and customized quizzes by chapter or exam domain